2018
DOI: 10.2147/jaa.s170866
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with severe, uncontrolled, eosinophilic asthma enrolled in a French cohort

Abstract: Background and objectiveBenralizumab (Fasenra™) has recently been approved as add-on maintenance treatment for adult patients with severe eosinophilic asthma inadequately controlled despite high-dosage inhaled corticosteroids plus long-acting β2-agonists. We aimed to identify and describe the clinical characteristics and disease burden of patients with severe, uncontrolled, eosinophilic asthma in France who may be eligible for treatment with benralizumab.Patients and methodsThis was a retrospective analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This study expands upon the previous finding of low overall omalizumab use by finding similar low utilization rates for the 4 more recently introduced asthma biologics (4). The percentage of individuals with severe asthma who would be eligible to use asthma biologics (7,8) is likely to be several times higher than the use rates we identified in this study. This suggests that asthma biologics are not being used by many individuals who have frequent exacerbations and would benefit by having them reduced.…”
Section: Discussionmentioning
confidence: 70%
“…This study expands upon the previous finding of low overall omalizumab use by finding similar low utilization rates for the 4 more recently introduced asthma biologics (4). The percentage of individuals with severe asthma who would be eligible to use asthma biologics (7,8) is likely to be several times higher than the use rates we identified in this study. This suggests that asthma biologics are not being used by many individuals who have frequent exacerbations and would benefit by having them reduced.…”
Section: Discussionmentioning
confidence: 70%
“…In 10 studies [37,51,70,72,78,87,[97][98][99][100] reporting the proportion of patients with any asthma-related exacerbation (i.e. moderate, severe, not-specified) at baseline, there was a wide range in the proportion of patients that experienced at least one exacerbation, from 14.9% (n = 737) [87] in patients with moderate/severe uncontrolled asthma initiating omalizumab to 100.0% (n = 25,935) [100] in patients with persistent asthma in a managed care setting.…”
Section: Exacerbationsmentioning
confidence: 99%
“…The SLR identified 54 studies that reported asthma-related HCRU such as healthcare visits and hospitalisations [18,21,28,33,35,37,47,57,[59][60][61][62]65,[69][70][71][72][73]75,77,[86][87][88][89]92,93,95,97,98,[100][101][102]105,. Lack of asthma control despite treatment with ICS/LABA, and pre-treatment prior to omalizumab including with OCS, ICS, ICS/LABA, leukotriene receptor Fig.…”
Section: Economic Burden 351 Healthcare Resource Utilizationmentioning
confidence: 99%
“…1,2 Those with severe asthma have more symptoms, exacerbations and comorbidities compared to those with mild-to-moderate asthma. [3][4][5] They also have lower asthma control, quality of life and lung function despite high doses of ICS. 3,[6][7][8] As the severity of asthma increases, so do the costs for society, 9,10 and severe uncontrolled asthma accounts for 60% of all asthma costs.…”
Section: Introductionmentioning
confidence: 99%